Temperature-sensitive hydrophilic-hydrophobic reversible conversion low-temperature regenerated moisture absorption material as well as preparation method and application of temperature-sensitive hydrophilic-hydrophobic reversible conversion low-temperature regenerated moisture absorption material

Through the low-temperature regeneration of hygroscopic absorbent materials with reversible conversion of temperature-sensitive hydrophilic and reversible conversion, combining temperature-sensitive monomers, hydrophilic monomers and inorganic salts, the problem of limited hygroscopic absorbance in high humidity environments is solved, and the recycling of high-efficiency hygroscopic absorbance and low-temperature desorption is achieved. It adapts to different humidity environments, and the preparation method is simple and easy to perform.

CN120441755APending Publication Date: 2025-08-08SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202510348962.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

The existing hygroscopic absorbent materials have limited hygroscopic ability in high humidity environments, high regeneration temperature, poor recycling performance, high preparation cost, and difficult to meet practical application needs.

Method used

A low-temperature regenerated hygroscopic material with a temperature-sensitive hydrophilic and reversible conversion is adopted. The temperature-sensitive monomer N-isopropyl acrylamide and the hydrophilic monomer 2-acrylamide-2-methylpropanesulfonic acid copolymer are combined with inorganic salt calcium chloride to form a ternary system, which realizes the reversible conversion of the material at low temperature and has high moisture absorption rate and low temperature desorption properties.

Benefits of technology

The material absorbs moisture efficiently at room temperature and desorbs quickly at hydrophobic state at 50°C to achieve efficient recycling of the material. It has excellent moisture absorption performance and low-temperature regeneration ability, adapts to different humidity environments, and is simple and easy to prepare.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120441755A_ABST
    Figure CN120441755A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of moisture absorption materials, and discloses a temperature-sensitive hydrophilic-hydrophobic reversible conversion low-temperature regenerated moisture absorption material and a preparation method and application thereof. The temperature-sensitive hydrophilic-hydrophobic reversible conversion low-temperature regenerated moisture absorption material comprises a polymer matrix and inorganic salt, the polymer matrix is a copolymer of a temperature-sensitive monomer and a hydrophilic monomer, and the inorganic salt is loaded inside and on the surface of the polymer matrix. The hygroscopic material prepared by the method has reversible transition from a hydrophilic state to a hydrophobic state near the lowest phase transition critical temperature; the material is in a hydrophilic state during moisture absorption and is in a hydrophobic state during desorption, and the material has excellent moisture absorption performance and low-temperature desorption regeneration performance; the lowest phase transition critical temperature can be adjusted according to actual requirements to adapt to different moisture absorption application scenes, the polymer gel moisture absorption material is a ternary system, the three components achieve breakthrough improvement of the moisture absorption-desorption performance through the multi-stage synergistic effect, and a new normal form is provided for environment self-adaptive material design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hygroscopic materials, and in particular relates to a temperature-sensitive, hydrophilic-hydrophobic reversible conversion low-temperature regenerated hygroscopic material, and a preparation method and application thereof. Background Art

[0002] High humidity has a range of adverse effects on human health, living comfort, industrial manufacturing processes, and agricultural production. From a medical perspective, high humidity exacerbates respiratory symptoms and promotes the proliferation of microorganisms such as mold and bacteria, thereby increasing the incidence of infectious diseases. Regarding indoor environmental quality, high humidity creates a stuffy feeling in living and working spaces, accelerates the degradation of building materials, and thus affects the durability of structures. In industrial manufacturing, high humidity poses a threat to product quality, causing electronic equipment failures and impacting the stability of chemical products, negatively impacting production efficiency and economic benefits. In agriculture, high humidity inhibits crop growth, increases the incidence of disease, and impacts the sustainability of agricultural production. Furthermore, high humidity increases energy consumption, as additional energy is required to maintain suitable indoor temperature and humidity conditions.

[0003] Given the adverse effects of excessive humidity on human health, living comfort, industrial manufacturing processes, and agricultural production, it is urgent to implement necessary dehumidification measures to control humidity. Compared to other dehumidification technologies, such as air conditioning systems and dehumidifiers, dehumidification with dehumidifiers offers advantages such as portability, low cost, high moisture absorption capacity, safety, environmental protection, and renewability. Common desiccant desiccant options include liquid and solid desiccant. Liquid desiccant desiccant options are limited in their application due to drawbacks such as corrosiveness and toxicity. Commonly used solid desiccant desiccant options include zeolite, silica gel, and activated carbon. These materials have limited moisture absorption capacity, high regeneration temperatures, and poor recyclability. New solid desiccant desiccant materials have been a focus of research in recent years. For example, metal-organic frameworks (MOFs), due to their unique pore structure and high specific surface area, possess high water vapor adsorption capacity, making them promising candidates for desiccant applications. However, these materials generally suffer from poor water stability and prone to hydrolysis, leading to structural collapse. Furthermore, their preparation is costly and complex, making them unsuitable for practical applications. Due to their highly tunable physical structure and chemical properties, polymer gel hygroscopic materials can store water molecules within the gel through the swelling of a three-dimensional network, preventing liquid leakage. In recent years, a series of hygroscopic polymer gel materials have been developed by combining inorganic salts with excellent hygroscopic properties with highly hydrophilic polymer gels. These materials effectively control humidity and mitigate the adverse effects of high humidity environments.

[0004] Patent CN115920602A discloses a light-driven, highly hygroscopic composite atmospheric water-collecting material, its preparation method, and applications. This hygroscopic gel can effectively capture moisture molecules from the air, thereby generating freshwater resources. However, this hygroscopic gel uses lithium chloride to enhance its adsorption properties, which is relatively expensive compared to common hygroscopic agents, making it difficult to implement on a large scale.

[0005] Patent CN117582934A discloses a method for preparing and applying an atmospheric water-absorbing polymeric material, as well as a method for collecting atmospheric water. This method utilizes freeze-drying to prepare the adsorbent polymeric material, achieving a moisture absorption capacity of approximately 1.6 g / g at low humidity, significantly improving the material's hygroscopic properties. However, freeze-drying has long cycles and high energy consumption, and the freeze dryer is expensive, requiring a vacuum system and a cryogenic system, significantly increasing costs.

[0006] Patent CN115738619A discloses a composite solid dehumidifier, its preparation method, and the dehumidifier. This composite solid dehumidifier exhibits rapid and robust moisture absorption, high moisture absorption capacity, and is not susceptible to deliquesce and liquefaction. It also eliminates the risk of secondary brine contamination. It also exhibits good dehumidification performance even at low ambient humidity, making it suitable for dehumidification applications in varying humidity environments. However, the desorption and regeneration temperature, desorption rate, and desorption and regeneration rate of this composite solid dehumidifier are not specified.

[0007] Patent CN116693928A discloses a method for preparing a photothermal hygroscopic polymer gel. This gel exhibits excellent photothermal conversion performance and moisture absorption / desorption kinetics, enabling rapid moisture collection, desorption, and regeneration across a wide temperature and humidity range. However, the preparation method provided by this technical solution is cumbersome and complex, making it unsuitable for practical production.

[0008] Therefore, it is of positive practical significance to provide a polymer gel hygroscopic material with simple process, excellent moisture absorption and desorption performance and high efficiency cycle stability. Summary of the Invention

[0009] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a temperature-sensitive, low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion.

[0010] Another object of the present invention is to provide a method for preparing a temperature-sensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion.

[0011] Another object of the present invention is to provide application of the above-mentioned hygroscopic material in the field of air dehumidification.

[0012] The purpose of the present invention is achieved through the following technical solutions:

[0013] A thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion, comprising a polymer matrix and an inorganic salt;

[0014] The polymer matrix is a copolymer of a thermosensitive monomer and a hydrophilic monomer, and the inorganic salt is uniformly loaded inside and on the surface of the polymer matrix.

[0015] Preferably, the temperature-sensitive monomer is at least one of N-vinylcaprolactam, N,N-diethylacrylamide, 2-(2-methoxyethoxy)ethyl methacrylate, and N-isopropylacrylamide.

[0016] The hydrophilic monomer is at least one of sodium p-styrene sulfonate, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and N-vinyl pyrrolidone;

[0017] The inorganic salt is at least one of calcium chloride and lithium chloride.

[0018] Preferably, the mass ratio of the thermosensitive monomer, the hydrophilic monomer and the inorganic salt is (1.0-4.5):(0.5-4.0):(1.0-5.0), more preferably (1.5-4.5):(0.5-3.5):5.0.

[0019] Preferably, the temperature-sensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic switching further comprises a cross-linking agent, an initiator and water.

[0020] Preferably, the temperature-sensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion comprises, by mass percentage, 1 to 50% N-isopropylacrylamide, 1 to 50% 2-acrylamide-2-methylpropanesulfonic acid, 20 to 50% inorganic hygroscopic salt, 0.1 to 1% cross-linking agent, 0.1 to 1% initiator, and the balance is water.

[0021] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion comprises the following steps:

[0022] (1) dissolving a thermosensitive monomer, a hydrophilic monomer, and a cross-linking agent in water and stirring uniformly to obtain a solution A;

[0023] (2) adding an initiator to solution A and stirring uniformly to polymerize to obtain a polymer matrix;

[0024] (3) The polymer matrix is washed, then immersed in an inorganic salt solution and dried to obtain a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion.

[0025] Preferably, the cross-linking agent in step (1) is one of N,N'-methylenebisacrylamide, polyethylene glycol or N,N'-bis(acryloyl)cystamine, and the added amount is 0.1-10% of the total mass of the temperature-sensitive monomer and the hydrophilic monomer, preferably 0.5-5%;

[0026] The initiator in step (2) is one of ammonium persulfate, potassium persulfate, α-ketoglutaric acid or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and the added amount is 0.1-6% of the total mass of the temperature-sensitive monomer and the hydrophilic monomer.

[0027] Preferably, the polymerization in step (2) is thermal polymerization or photopolymerization;

[0028] The thermal polymerization temperature is 30-90°C and the polymerization time is 0.5-10h;

[0029] The wavelength of the photopolymerization irradiation light is 250-400 nm, and the irradiation time is 0.1-3 hours.

[0030] Preferably, the specific method of washing in step (3) is to soak in deionized water for 10 to 72 hours, during which the water is changed 1 to 3 times.

[0031] Preferably, the mass concentration of the inorganic salt solution in step (3) is 1 to 10 wt %; the soaking time is 10 to 72 h; the drying temperature is 50 to 90° C.; and the drying time is 2 to 12 h.

[0032] The application of the above-mentioned temperature-sensitive hydrophilic-hydrophobic reversible conversion low-temperature regenerated hygroscopic material in air dehumidification.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0034] (1) It has the characteristics of reversible hydrophilic and hydrophobic conversion and low-temperature regeneration

[0035] The present invention introduces the thermosensitive monomer N-isopropylacrylamide. The single polymer of this molecule has special thermosensitive properties, and its lower critical solution temperature (lowest phase transition temperature) is usually around 32°C. When it is below this temperature, the polymer hydrogel becomes hydrophilic; when the temperature rises above the lower critical solution temperature, the polymer hydrogel becomes hydrophobic. To meet the needs of practical applications, the present invention introduces the hydrophilic monomer 2-acrylamide-2-methylpropanesulfonic acid to adjust the lowest phase transition temperature to around 50°C. When absorbing moisture at room temperature, the material is in a hydrophilic state, and the gel network is highly swollen, which is conducive to the diffusion of water molecules within the gel, increasing the material's moisture absorption rate and moisture absorption capacity; when desorption and regeneration are carried out, the material only needs to be at a relatively low temperature of around 50°C for it to become hydrophobic, and the gel network structure shrinks, which is conducive to the discharge of water molecules from the gel in the form of liquid water, increasing the material's desorption rate and ultimately achieving complete desorption and regeneration. This transformation process is reversible. When the temperature drops, the material can return to a hydrophilic state, that is, the hygroscopic material can be recycled.

[0036] (2) Improve the loading rate and loading intensity of inorganic hygroscopic salts

[0037] The present invention introduces a multifunctional water-soluble anionic monomer, 2-acrylamide-2-methylpropanesulfonic acid. The sulfonic acid groups in the monomer molecule and its polymer chain are strongly anionic and water-soluble. Due to the electrostatic attraction between the strongly anionic sulfonic acid groups in the polymer chain and the cations of the inorganic hygroscopic salt, the cations accumulate around the sulfonic acid groups in the polymer chain segments to form an ionic layer, thereby increasing the loading rate and loading strength of the inorganic hygroscopic salt. In addition, the strong electrostatic repulsion between the sulfonic acid groups causes the gel network structure to expand, thus endowing the polymer gel material with a high water molecule loading capacity and further improving the material's hygroscopic properties.

[0038] (3) The lowest phase transition temperature of polymer gel hygroscopic materials can be adjusted

[0039] The hydrophilic-hydrophobic reversible switchable polymer hygroscopic material described in this invention can be customized based on the optimal temperature requirements for moisture absorption and desorption performance in practical applications. By precisely controlling the ratio of 2-acrylamide-2-methylpropanesulfonic acid and N-isopropylacrylamide, a polymer hygroscopic material with a specific minimum phase transition temperature can be synthesized. This allows for precise control of the material's hydrophilic-hydrophobic reversible switchable properties, providing optimal moisture absorption and desorption performance to suit different application scenarios and enhance practicality.

[0040] (4) The ternary system achieves synergistic efficiency of moisture absorption and desorption

[0041] The polymer gel hygroscopic material of the present invention is a ternary system, and the three components achieve a breakthrough improvement in moisture absorption and desorption performance through multi-level synergistic action. The thermosensitive monomer acts as a thermosensitive "dynamic switch", and its minimum phase transition temperature is adjusted by the ion shielding effect of the hygroscopic salt cations, so that the material can trigger hydrophobic contraction in the actual required temperature environment and squeeze the pores for rapid desorption; the strong anionic hydrophilic groups of the hydrophilic monomer efficiently adsorb moisture through strong hydrogen bonds and ion-dipole effects, while the hygroscopic salt cations form an ionic cross-linked network, which not only enhances mechanical strength but also anchors the hygroscopic salt to prevent loss; the hygroscopic salt breaks through the traditional hygroscopic limit through the strong hydration of cations and anions, and cooperates with the thermosensitive monomer to reduce the phase change energy consumption. The synergistic performance of the three is as follows: at low temperature and high humidity, the hydrophilic monomer and the hygroscopic salt dominate the adsorption, and the thermosensitive monomer molecular chain swells to maintain the porous structure; at high temperature and low humidity, the hydrophobic contraction of the thermosensitive monomer and the salting-out effect of the hygroscopic salt cations synergistically drive the release of water, while the hydrophilic monomer network inhibits structural collapse. Furthermore, the hydrophobic barrier of the thermosensitive monomer and the strong anionic groups of the hydrophilic monomer work together to resist deliquescence caused by hygroscopic salts, enabling the material to maintain high performance after multiple cycles. This system demonstrates the trinity of "adsorption-desorption-anti-aging" advantages in intelligent dehumidification, providing a new paradigm for the design of environmentally adaptive materials.

[0042] (5) The preparation method is simple, the raw materials are readily available, and it is suitable for large-scale production

[0043] The raw materials required for the polymer gel hygroscopic material of the present invention are easily available and widely sourced, and the preparation method is simple and easy. There are two optional polymerization methods, one is the conventional and convenient free radical thermal polymerization, which has the advantages of simple operation and low cost, and is carried out under relatively mild conditions and is easy to control. The other light polymerization method is environmentally friendly, not only has wide adaptability, low cost, and low energy consumption, but also has good spatial and temporal controllability and fast polymerization and curing speed; by controlling the light intensity and time, precise control of the physical and chemical properties of the polymerization reaction can also be achieved. The adsorption and desorption properties of the temperature-sensitive polymer hygroscopic materials prepared by the two polymerization methods are not much different, and the polymerization method can be flexibly selected according to actual needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 These are the actual pictures and scanning electron microscope pictures of the polymer hygroscopic materials prepared in Example 3, Example 4 and Comparative Example 3.

[0045] Figure 2 The following are Fourier transform infrared spectra of Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3.

[0046] Figure 3 The moisture absorption curves of Example, Comparative Example, commercial color-changing silica gel and 13X molecular sieve within 48 hours under the conditions of 90% RH and 27°C.

[0047] Figure 4 The desorption curves of Example, Comparative Example, commercial color-changing silica gel and 13X molecular sieve at 50°C within 11 hours.

[0048] Figure 5 The DSC curves of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and calcium chloride were obtained by differential scanning calorimetry.

[0049] Figure 6 The surface contact angles of Example 3 and Example 4 were measured at 27° C. and 50° C. using a contact angle meter. DETAILED DESCRIPTION

[0050] The present invention will be described in further detail below with reference to specific examples, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0051] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available unless otherwise specified.

[0052] Example 1

[0053] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0054] (1) Dissolve N-isopropylacrylamide (4.50 g), 2-acrylamide-2-methylpropanesulfonic acid (0.50 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0055] (2) adding ammonium persulfate (0.10 g) as an initiator to the mixed solution and stirring the mixture at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0056] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 4.5:0.5:5.0.

[0057] Example 2

[0058] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0059] (1) Dissolve N-isopropylacrylamide (4.00 g), 2-acrylamide-2-methylpropanesulfonic acid (1.00 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0060] (2) adding ammonium persulfate (0.10 g) as an initiator to the mixed solution and stirring the mixture at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0061] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a low-temperature regenerated hygroscopic material based on reversible hydrophilic-hydrophobic conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 4:1:5.

[0062] Example 3

[0063] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0064] (1) Dissolve N-isopropylacrylamide (2.50 g), 2-acrylamide-2-methylpropanesulfonic acid (2.50 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0065] (2) adding ammonium persulfate (0.10 g) as an initiator to the mixed solution and stirring the mixture at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0066] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a low-temperature regenerated hygroscopic material based on reversible hydrophilic-hydrophobic conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 2.5:2.5:5.0.

[0067] Example 4

[0068] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0069] (1) Dissolve N-isopropylacrylamide (2.50 g), 2-acrylamide-2-methylpropanesulfonic acid (2.50 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0070] (2) adding a photoinitiator, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (0.10 g), to the mixed solution and stirring at room temperature, followed by polymerization under ultraviolet light for 0.5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0071] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a low-temperature regenerated hygroscopic material based on reversible hydrophilic-hydrophobic conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 2.5:2.5:5.0.

[0072] Example 5

[0073] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0074] (1) Dissolve N-isopropylacrylamide (2.00 g), 2-acrylamide-2-methylpropanesulfonic acid (3.00 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0075] (2) adding a photoinitiator, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (0.10 g), to the mixed solution and stirring at room temperature, followed by polymerization under ultraviolet light for 0.5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0076] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a low-temperature regenerated hygroscopic material based on reversible hydrophilic-hydrophobic conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 2:3:5.

[0077] Example 6

[0078] A method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion, comprising the following steps:

[0079] (1) Dissolve N-isopropylacrylamide (1.50 g), 2-acrylamide-2-methylpropanesulfonic acid (3.50 g), and crosslinker N,N'-methylenebisacrylamide (0.18 g) in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution;

[0080] (2) adding a photoinitiator, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (0.10 g), to the mixed solution and stirring at room temperature, followed by polymerization under ultraviolet light for 0.5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0081] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours, and then dried in a 70°C oven for 12 hours to obtain a low-temperature regenerated hygroscopic material based on reversible hydrophilic-hydrophobic conversion. The mass ratio of the three components N-isopropylacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and inorganic salt calcium chloride was 1.5:3.5:5.0.

[0082] Example 7

[0083] The difference between Example 3 and Example 3 is that the temperature-sensitive monomer is N,N-diethylacrylamide.

[0084] Example 8

[0085] The difference between Example 3 and Example 3 is that the hydrophilic monomer is sodium p-styrene sulfonate.

[0086] Comparative Example 1

[0087] (1) Dissolve the monomer N-isopropylacrylamide (5.00 g) and the cross-linking agent N,N'-methylenebisacrylamide (0.18 g) in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution;

[0088] (2) adding the initiator ammonium persulfate (0.10 g) to the mixed solution and stirring at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain poly(N-isopropylacrylamide) hydrogel;

[0089] (3) The poly(N-isopropylacrylamide) hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours. The washed hydrogel was then dried in an oven at 70°C for 12 hours to obtain a polymer hygroscopic material.

[0090] Comparative Example 2

[0091] (1) Dissolve 2-acrylamide-2-methylpropanesulfonic acid (5.00 g) and N,N'-methylenebisacrylamide (0.18 g) in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0092] (2) adding ammonium persulfate (0.10 g) as an initiator to the mixed solution and stirring it at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain poly(2-acrylamide-2-methylpropanesulfonic acid) hydrogel;

[0093] (3) The poly(2-acrylamide-2-methylpropanesulfonic acid) hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed hydrogel was then transferred to an inorganic salt calcium chloride aqueous solution (concentration 5 wt%) and soaked for 24 hours. The washed hydrogel was then dried in an oven at 70°C for 12 hours to obtain a polymer hygroscopic material.

[0094] Comparative Example 3

[0095] (1) Dissolve N-isopropylacrylamide (2.50 g), 2-acrylamide-2-methylpropanesulfonic acid (2.50 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0096] (2) adding ammonium persulfate (0.10 g) as an initiator to the mixed solution and stirring the mixture at room temperature, followed by polymerization in a water bath at 70°C for 5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0097] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by immersing in deionized water for 24 h, during which the water was changed three times. The hydrogel was then dried in an oven at 70°C for 12 h to obtain a polymer hygroscopic material.

[0098] Comparative Example 4

[0099] (1) Dissolve N-isopropylacrylamide (1.00 g), 2-acrylamide-2-methylpropanesulfonic acid (4.00 g), and N,N'-methylenebisacrylamide (0.18 g), a crosslinker, in 100 ml of water and stir at room temperature for 0.5 h to obtain a uniform mixed solution.

[0100] (2) adding a photoinitiator, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (0.10 g), to the mixed solution and stirring at room temperature, followed by polymerization under ultraviolet light for 0.5 h to obtain a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel;

[0101] (3) The poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer hydrogel was washed by soaking in deionized water for 24 hours, during which the water was changed three times. The washed copolymer hydrogel was then transferred to an inorganic salt aqueous solution of calcium chloride (concentration 5 wt%) and soaked for 24 hours. The washed copolymer hydrogel was then dried in an oven at 70°C for 12 hours to obtain a polymer hygroscopic material.

[0102] Test Case

[0103] (1) Material characterization

[0104] Figure 1The following are photos and scanning electron micrographs of the hygroscopic hydrogel materials prepared in Example 3, Example 4, and Comparative Example 3. The photos show that Examples 3 and 4 present uniform white particles with no noticeable color difference or impurities. The particles are irregularly shaped, exhibiting a naturally formed rough surface structure. The scanning electron micrographs, magnified 1000x, reveal that the microscopic surfaces of Examples 3 and 4 are uneven, with numerous grooves. A large number of small calcium chloride particles are evenly distributed on the surface, with some embedded within the gel, resulting in noticeable protrusions on the surface. The photos of Comparative Example 3 show a dense surface with few pores, exhibiting a smooth surface structure, and are pale yellow, translucent gel particles. The scanning electron micrographs of Comparative Example 3, magnified 1000x, show a smooth, dense surface with no protrusions or small particles. From this analysis, it can be seen that the rough surfaces and the uniform distribution of small calcium chloride particles within and on the surface of the gel in Examples 3 and 4 contribute to improved hygroscopicity.

[0105] Figure 2 The Fourier transform infrared spectra of Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in FIG. As can be seen from the figure, in Comparative Example 1, 2972 cm -1 and 1651cm -1 The stretching vibrations of C=O in the isopropyl group and C=O in the amide group are respectively attributed to each other; in Comparative Example 2, 1209 cm -1 and 1041cm -1 They are respectively attributed to the S=O antisymmetric stretching vibration and SO symmetric stretching vibration in the sulfonic acid group, and together constitute the characteristic peak pair of the sulfonic acid group; in Comparative Example 3 and Example 4, the characteristic peaks of Comparative Example 1 and Comparative Example 2 are present at the same time, proving that Comparative Example 3 and Example 3 contain poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer. Other peak positions such as 3405 cm -1 It is attributed to OH stretching vibration, which may come from the residual water molecules in the material. It is observed in all samples, but Ca 2+ The introduction of NH4Cl2 enhances the hydrophilicity of the material, which is shown by the 3405 cm -1 In addition, by comparison, it can be found that the OH peak intensity at 1651cm is significantly increased in Example 4, Comparative Example 1 and Comparative Example 2 loaded with CaCl2 compared with Comparative Example 3 without CaCl2. -1 The C=O peak position in the amide group is red-shifted, which can be attributed to the Ca 2+ The electrostatic interaction with the C=O of the amide group affects the amide-related peak; while 1041cm -1 The SO peak position of the sulfonic acid group at the bottom of the sulfonic acid group undergoes a blue shift, which is due to the Ca 2+These spectral characteristics are caused by the coordination and strong electrostatic interaction with the sulfonic acid group. 2 The coordination and strong electrostatic interaction with the sulfonic acid group provide direct evidence and also reflect the chemical bond characteristics of each component in the material, proving that Example 4 is a poly(N-isopropylacrylamide)-poly(2-acrylamide-2-methylpropanesulfonic acid) copolymer composite hygroscopic material.

[0106] (2) Performance testing

[0107] Moisture absorption test: weigh the mass of the sample to be tested after drying, recorded as M d , unit is g. Place the completely dried sample to be tested in a constant temperature and humidity chamber (90% RH and 27°C) and weigh the weight of each sample after moisture absorption at regular intervals, record it as M w , in g. Using a nonlinear reading, weigh the sample every hour for the first 11 hours, once at the 13th hour, every 4 hours from 24 to 36 hours, and once at the end of the final 48 hours. Calculate the relative moisture absorption of each sample after each weighing in g / g. The relative moisture absorption calculation method is shown in Equation 1.

[0108]

[0109] Figure 3 The following are the moisture absorption curves of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, commercial desiccant color-changing silica gel and 13X molecular sieve under the working conditions of 90% RH and 27°C for 48 hours. From the moisture absorption test results, it is known that the 48-hour maximum relative moisture absorption capacity is ranked from high to low as Example 4 (2.17 g / g), Example 3 (1.97 g / g), Example 5 (1.82 g / g), Example 6 (1.60 g / g), Comparative Example 2 (1.50 g / g), Comparative Example 4 (1.41 g / g), Example 2 (1.02 g / g), Example 1 (0.64 g / g), Comparative Example 3 (0.59 g / g), Comparative Example 1 (0.37 g / g), 13X molecular sieve (0.28 g / g), and color-changing silica gel (0.28 g / g). The above moisture absorption test results show that Examples 3, 4, 5, and 6 with suitable component ratios not only have a high moisture absorption rate, but also have a high moisture absorption capacity. Compared with Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, 13X molecular sieve, and color-changing silica gel, they have better moisture absorption capacity and are more excellent moisture-absorbing materials.

[0110] Desorption test: weigh the mass of the sample after complete drying, recorded as M d , in g. Weigh the final weight of each sample at the end of the moisture absorption test and record it as M f, unit is g. After the moisture absorption test, put each sample into a 50℃ oven and weigh the weight of the sample after desorption every once in a while, record it as M n , unit is g. At the same time, calculate the relative water content of each sample, unit is %. The relative water content calculation method is as follows

[0111] As shown in formula 2.

[0112]

[0113] Figure 4 The desorption curves of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, commercial desiccant color-changing silica gel, and 13X molecular sieve in a 50°C oven for 11 hours are shown. From the desorption results, it is known that the relative water contents at 3 hours are, from low to high, Example 1 (2.36%), Example 4 (3.96%), Example 3 (4.27%), Example 6 (8.02%), Example 5 (8.43%), Comparative Example 2 (11.13%), Example 2 (12.20%), Comparative Example 3 (13.46%), Comparative Example 4 (14.02%), color-changing silica gel (17.51%), Comparative Example 1 (21.92%), and 13X molecular sieve (88.02%). This shows that Example 1, Example 4 and Example 3 have extremely excellent desorption performance, and the relative water content can be reduced to less than 5% in just 3 hours, basically achieving complete regeneration, and Example 6, Example 5, and Example 2 also have better desorption performance than the commercial desiccant color-changing silica gel, and the desorption performance of all examples is far better than 13X molecular sieve. At the end of 11h desorption, the relative water content of Example 4 (0.01%), Example 3 (0.08%), Example 1 (0.11%), Example 5 (0.15%) and Example 6 (0.58%) is less than 0.6%, which is better than Comparative Example 2 (0.77%), Comparative Example 4 (0.93%), Comparative Example 3 (1.12%), Example 2 (2.00%) and Comparative Example 1 (5.15%), and is far better than commercial desiccant color-changing silica gel (12.5%) and 13X molecular sieve (85.47%). The above desorption test results show that Example 4 and Example 3, Example 1, Example 5 and Example 6 with appropriate component ratios can basically achieve complete desorption and regeneration within 11 hours at 50°C, and the desorption effect and desorption rate are overall better than those of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, color-changing silica gel and 13X molecular sieve. They are hygroscopic materials with excellent desorption performance and can achieve complete desorption and regeneration at low temperature.

[0114] Figure 5The following are differential scanning calorimeter (DSC) curves for Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and calcium chloride. As can be seen from the figure, Example 1 exhibits a significant endothermic peak at approximately 40-46°C, demonstrating a thermal response effect, indicating that the sample undergoes a significant volume phase transition within this temperature range. Example 2 also exhibits an absorption peak within the same temperature range, but its intensity is lower than that of Example 1, indicating that Example 2's thermal response is relatively weak. Similarly, Example 3 exhibits similar endothermic behavior near the same temperature range, but the endothermic peak is much weaker. Comparative Example 1 shows a clear inflection point around 32°C, with a sharp increase in the endothermic rate, followed by a strong endothermic peak. This is consistent with the lower critical solution temperature of the thermosensitive polymer poly(N-isopropylacrylamide) at around 32°C; at this temperature, the polymer undergoes a hydrophilic to hydrophobic transition and exhibits a significant phase volume transition. Comparative Example 2, on the other hand, exhibits a relatively stable heat flow throughout the entire tested temperature range, with no significant endothermic peak. Similarly, the heat flow of calcium chloride varies minimally across the entire temperature range, almost forming a straight line. The above test results show that Examples 1, 2 and 3 exhibit thermosensitive properties to varying degrees. Within a certain temperature range, the gel network undergoes a phase transition process of hydrophilic-hydrophobic conversion and volume shrinkage, which is conducive to the accelerated completion of the desorption process of the hygroscopic material; and the temperature range in which this process occurs and the intensity of the thermal response can be adjusted according to the different ratios of the two monomers in the preparation process, so that the material can adapt to different application scenarios.

[0115] Figure 6 The surface contact angles of Examples 3 and 4 were measured using a contact angle meter at 27°C and 50°C, respectively. The results show that at 27°C, the contact angles of Examples 3 and 4 were 64.4° and 62.8°, respectively, indicating a hydrophilic state. However, after heating to 50°C, the contact angles were 106.5° and 121.1°, respectively, indicating a hydrophobic state. This indicates a temperature-dependent shift in the hydrophilic and hydrophobic properties of the materials. This shift facilitates rapid water desorption, improving the desorption rate and regeneration efficiency.

[0116] The above embodiments are only preferred embodiments of the present invention. The scope of implementation of the present invention is not limited by the above embodiments. Without departing from the design spirit of the present invention, any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion, characterized in that: including a polymer matrix and an inorganic salt; The polymer matrix is a copolymer of a thermosensitive monomer and a hydrophilic monomer, and the inorganic salt is loaded inside and on the surface of the polymer matrix.

2. The thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion according to claim 1, characterized in that: The temperature-sensitive monomer is at least one of N-vinyl caprolactam, N,N-diethylacrylamide, 2-(2-methoxyethoxy)ethyl methacrylate, and N-isopropylacrylamide. The hydrophilic monomer is at least one of sodium p-styrene sulfonate, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and N-vinyl pyrrolidone; The inorganic salt is at least one of calcium chloride and lithium chloride.

3. The thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion according to claim 1, characterized in that: The mass ratio of the temperature-sensitive monomer, the hydrophilic monomer and the inorganic salt is 1.0-4.5:0.5-4.0:1.0-5.

0.

4. The thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion according to claim 1, characterized in that: The temperature-sensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion further comprises a cross-linking agent, an initiator and water.

5. A method for preparing the thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving a thermosensitive monomer, a hydrophilic monomer, and a cross-linking agent in water and stirring uniformly to obtain a solution A; (2) adding an initiator to solution A and stirring uniformly to polymerize to obtain a polymer matrix; (3) The polymer matrix is washed, then immersed in an inorganic salt solution, and dried to obtain a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic conversion.

6. The method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic switching according to claim 5, characterized in that: The cross-linking agent in step (1) is one of N,N'-methylenebisacrylamide, polyethylene glycol or N,N'-bis(acryloyl)cystamine, and the added amount is 0.1-10% of the total mass of the temperature-sensitive monomer and the hydrophilic monomer; The initiator in step (2) is one of ammonium persulfate, potassium persulfate, α-ketoglutaric acid or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and the added amount is 0.1-6% of the total mass of the temperature-sensitive monomer and the hydrophilic monomer.

7. The method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic switching according to claim 5, characterized in that: The polymerization in step (2) is thermal polymerization or photopolymerization; The thermal polymerization temperature is 30-90°C and the polymerization time is 0.5-10h; The wavelength of the photopolymerization irradiation light is 250-400 nm, and the irradiation time is 0.1-3 hours.

8. The method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic switching according to claim 5, characterized in that: The washing in step (3) is performed by soaking in deionized water for 10 to 72 hours, during which the water is changed 1 to 3 times.

9. The method for preparing a thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilic and hydrophobic switching according to claim 5, characterized in that: The mass concentration of the inorganic salt solution in step (3) is 1 to 10 wt %; the soaking time is 10 to 72 hours; the drying temperature is 50 to 90° C.; and the drying time is 2 to 12 hours.

10. Use of the thermosensitive low-temperature regenerated hygroscopic material with reversible hydrophilicity and hydrophobicity conversion according to any one of claims 1 to 4 in air dehumidification.

Citation Information

Patent Citations

  • Preparation method and application of atmospheric water adsorption polymeric material and atmospheric water collection method

    CN117582934A

Cited By

  • CO2 pressure swing adsorption silica gel as well as preparation method and application thereof

    CN121130829A

  • Composite thermosensitive hydrogel as well as preparation method and regeneration method thereof

    CN121949875A